Pesan Dakwah Lagu Bismillah Cinta dalam Perspektif Semiotika Charles Morris - Alvin Khoiron; Fathimatuz Zahroh (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
This study aims to explain, in general, the song, the content of the da'wah message, and the urgency of the message in the current context through a qualitative approach and Charles Morris' semiotic theory approach. Based on the research results, the song Bismillah Cintahas ten lyric stanzas with five stanzas and repetition of song lyrics as an affirmation of meaning. The song has a message of da'wah so that people have faith in God and fellow human beings. The message also emphasizes the importance of high spirits, patience, sincerity in facing trials, and always giving positive energy in all things. The message of da'wah in the song's lyrics is essential to convey following the situation and conditions in Indonesia, which is being hit by a pandemic. This research has implications for the importance of various da'wah methods and media that can be filled with da'wah messages so that the song is also a means of da'wah, which is quite significant.